Resource conservation and productivity improvement under communal land tenure - Cossins, N.J. (Australian Academy of Science, 1986)
Summarizes the resource conservation and productivity improvement of African rangelands under communal land tenure. Presents data on livestock production in E. Africa & comparable regions, comparative costs of offtake & energy, comparative production per man-day and comparative production parameter among different pastoral systems and commercial ranches.